A potential contribution of altered cathepsin L expression to the development of dermal fibrosis and vasculopathy in systemic sclerosis. Issue 4 (11th February 2016) - Yamashita, Takashi; Asano, Yoshihide; Taniguchi, Takashi; Nakamura, Kouki; Saigusa, Ryosuke; Takahashi, Takehiro; Ichimura, Yohei; Toyama, Tetsuo; Yoshizaki, Ayumi; Miyagaki, Tomomitsu; Sugaya, Makoto; Sato, Shinichi
Abstract: Cathepsin L (CTSL) is a lysosomal proteolytic enzyme involved in inflammation and vascular and extracellular matrix remodelling, which are the three cardinal pathological events associated with systemic sclerosis (SSc). To elucidate the potential role of CTSL in the development of SSc, we here investigated CTSL expression in the lesional skin of patients with SSc and SSc animal models and the clinical correlation of serum CTSL levels. CTSL expression was elevated in dermal small vessels of SSc patients compared with those of healthy controls. Consistently, CTSL mRNA levels were increased in SSc lesional skin samples, but not in cultivated SSc dermal fibroblasts, compared with corresponding control samples from healthy individuals. Serum CTSL levels were significantly higher in SSc patients than in healthy controls and inversely correlated with skin score. Furthermore, the elevation of serum CTSL levels was linked to SSc vasculopathy. Supporting these results, Ctsl mRNA levels were decreased in the skin of bleomycin‐treated mice, an SSc animal model recapitulating its fibrotic aspect, and CTSL expression was enhanced in dermal small vessels of endothelial cell‐specific Fli1 knockout mice, reminiscent of SSc vasculopathy. Importantly, gene silencing of FLI 1 induced CTSL mRNA expression and Fli1 occupied the CTSL promoter in human dermal microvascular endothelial cells. Collectively, these results suggest that endothelial CTSL up‐regulation partially due to Fli1 deficiency may contribute to the development of vasculopathy, while the decrease in dermal CTSL expression is likely associated with dermal fibrosis in SSc.